2015
DOI: 10.5465/ambpp.2015.12729abstract
|View full text |Cite
|
Sign up to set email alerts
|

"Online Copyright Enforcement, Consumer Behavior, and Market Structure"

Abstract: It aims to provide evidence-based scientific support to the European policy-making process. The scientific output expressed does not imply a policy position of the European Commission. Neither the European Commission nor any person acting on behalf of the Commission is responsible for the use which might be made of this publication. Reproduction is authorised provided the source is acknowledged. All images © European AbstractTaking down copyright-infringing websites is a way to reduce consumption of pirated me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…On the demand side, efforts are being made to educate the public about the unethical and illegal nature of digital piracy (Gunter, 2009). Authorities have raided popular pirate sites such as Pirate Bay, Isohunt, Demonoid, BitTorrent, µTorrent, RARBG, LimeTorrents and Kickass Torrents, to name just a few, and have won many legal battles to shut down these sites on the internet (Aguiar et al , 2015). Despite these efforts, pirate websites are evolving and increasing.…”
Section: Introductionmentioning
confidence: 99%
“…On the demand side, efforts are being made to educate the public about the unethical and illegal nature of digital piracy (Gunter, 2009). Authorities have raided popular pirate sites such as Pirate Bay, Isohunt, Demonoid, BitTorrent, µTorrent, RARBG, LimeTorrents and Kickass Torrents, to name just a few, and have won many legal battles to shut down these sites on the internet (Aguiar et al , 2015). Despite these efforts, pirate websites are evolving and increasing.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that users simply found other ways to access the same pirated content on other popular sites. A study by Aguiar et al 2 using similar methods found similar results in that the shutdown of a single video-linking site Kino.to (now defunct) in Germany did not cause a meaningful increase in legal consumption. Notably, this shutdown was more like a website block than an actual site shutdown, because Kino.to linked to content only on other sites and did not host content; shutting down Kino.to simply removed, or "blocked," a means j Results from this 2015 study were therefore generated by 20 data points, an observation for each of 10 segments both before and after the blocks.…”
Section: Supply-side Anti-piracymentioning
confidence: 68%
“…As mentioned in Section 3.3, in equilibrium, the supply level, η, ought to depend on the level of supply-side enforcement, e. Accordingly, we now complete the model specification by endogenizing η using a standard break-even analysis in which players enter the market as long as there is profit to be made (e.g., Vickers 1989). Pirate suppliers are typically paid based on the number of downloads of pirated content uploaded by them (Aguiar et al 2015). The total advertisement revenue earned by all suppliers should then be proportional toq, the total number of illegal downloads; henceforth, without loss of generality, we assume this constant of proportionality to be one.…”
Section: Supplier Behavior and Subgame Equilibriummentioning
confidence: 99%
“…Our research questions and modeling approach put the spotlight squarely on how suppliers of pirated content actually operate, unraveling the mystery surrounding their business models. The underlying ecosystem shows a curious interdependence among aggregator sites, online ad agencies, and pirate suppliers (Aguiar et al 2015, Seidler 2011. In practice, many aggregator sites providing online access to pirated content operate on revenues generated through online advertisements.…”
Section: Introductionmentioning
confidence: 99%